2014
DOI: 10.1111/zph.12170
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Characterization of Salmonella enterica in Captive Wildlife and Exotic Animal Species in Ohio, USA

Abstract: The purpose of this study was to investigate the occurrence, antimicrobial resistance patterns, phenotypic and genotypic relatedness of Salmonella enterica recovered from captive wildlife host species and in the environment in Ohio, USA. A total of 319 samples including faecal (n = 225), feed (n = 38) and environmental (n = 56) were collected from 32 different wild and exotic animal species in captivity and their environment in Ohio. Salmonellae were isolated using conventional culture methods and tested for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 24 publications
(29 reference statements)
2
12
1
1
Order By: Relevance
“…Salmonella Heidelberg is predominantly associated with poultry (Foley et al, 2011), its occurrence in the present study is interesting since no intensive animal production activities were observed in the areas sampled suggesting other hosts such as wildlife as carriers of the pathogen (Botti et al, 2013;Farias et al, 2014). Salmonella Bsilla is a rarely found serovar and we are not aware of any outbreak report related to this organism in the literature.…”
Section: Contamination Of Irrigation Water Withmentioning
confidence: 54%
“…Salmonella Heidelberg is predominantly associated with poultry (Foley et al, 2011), its occurrence in the present study is interesting since no intensive animal production activities were observed in the areas sampled suggesting other hosts such as wildlife as carriers of the pathogen (Botti et al, 2013;Farias et al, 2014). Salmonella Bsilla is a rarely found serovar and we are not aware of any outbreak report related to this organism in the literature.…”
Section: Contamination Of Irrigation Water Withmentioning
confidence: 54%
“…In this phase, an exhaustive list of potential biological and physical hazards was created. The list of the zoonotic agents to be included was based on scientific reports of diseases in species involved in AVIs [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Animals Materials and Methodsmentioning
confidence: 99%
“… Disease Species Bibliography Tuberculosis Mycobacterium tuberculosis ; M. bovis [ 34 , 35 , 36 ] Brucellosis Brucella spp. [ 37 , 38 , 39 ] Salmonellosis Salmonella enterica [ 40 , 41 ] E. coli infections Escherichia coli [ 42 , 43 , 44 , 45 ] Campylobacteriosis Campylobacter spp. [ 46 ] Cryptosporidiosis Cryptosporidium muris [ 47 , 48 ] Listeriosis Listeria monocytogenes [ 49 ] Yersiniosis Yersinaia enterocolitica [ 49 ] Antimicrobial-Resistant bacteria MRSA (methicillin-resistant...…”
Section: Figure A1mentioning
confidence: 99%
“…En cuanto a la fauna silvestre, diversos reportes sugieren que la infección es prevalente en animales de ambientes acuáticos, incluyendo aves y mamíferos 56,57 , aunque se desconoce el efecto ecológico de la infección en estas poblaciones. De ellos, el grupo con un mayor número de evidencias como portadores de S. enterica son las aves, debido a que estos animales han recibido el interés de los organismos sanitarios por su capacidad para difundir patógenos zoonóticos altamente transmisibles 58,59 .…”
Section: La Fauna Silvestreunclassified